Indonesian representation in South Korean media during the Asian Games Jakarta – Palembang 2018 - Safira Ronasyifa; Didin Samsudin (Journal of Korean Applied Linguistics, 2022)
In August 2018, Indonesia hosted the Asian Games Jakarta – Palembang 2018. After hosting in 1962, Indonesia has had the theme "Asia's Energy", meaning that Indonesia is expected to be a source of energy support for some Asian countries on the world stage. The study aimed to discover the similarities and differences shown on the articles and how Indonesia is represented through lexicon, grammar, discourse practices, grammar, and discourse practices in online news articles written by the Korean Republic’s media. This study used a critical discourse analysis theory of Norman Fairclough with a descriptive qualitative method, developing critical discourse analysis based on formal-systemic linguistic assumptions. Based on the study results, it is observed that the published news articles during the opening were the articles giving a primary focus on Indonesia compared to the published articles during the event and closing, data was collected based on online news articles during the 2018 Jakarta Palembang Asian Games using a literature study of 15 articles. There is also a finding regarding text production in articles of Asian Games Jakarta-Palembang 2018 that were not influenced by outside intervention other than the media itself. Then, based on the text analysis results, it is discovered that Indonesian representations were divided into the viewpoint of a country and the viewpoint of the host of the Asian Games Jakarta Palembang 2018. In addition, the implications of this research are to find out Indonesia’s representation in the news media of the Republic of Korea during the 2018 Asian Games.